The Status of Sultan Mehmed Reşad’s Kadınefendis in the Harem: Hierarchy and Palace Representation - Lale Uçan (Yakın Dönem Türkiye Araştırmaları)
The 19th century marked significant social transformations, particularly in the structure of family life in major cities, reflecting the broader currents of change. When examining Sultan Mehmed Reşad’s palace during the Second Constitutional Era, a key point to consider is the absence of a vâlide sultan (queen mother) in the harem. This study explores the origins of the kadınefendis (consorts) and their integration into palace life within the hierarchical structure of the harem. By analyzing the kadınefendis’ roles in representing the palace, this research seeks to provide insight into the final form of this long-established institution. The study also examines the status of the kadınefendis in social life beyond the palace walls, drawing attention to the significance of their visits to various locations both within and outside the harem. These activities will be analyzed as extensions of their daily lives, highlighting their participation in the broader social fabric. Furthermore, the study situates Sultan Mehmed Reşad’s consorts within the context of women’s status in Ottoman society, exploring how their roles reflect the evolving dynamics of gender and social hierarchy during this transformative period.